Pyogenic Granuloma: A Case Report (Health Renaissance, 2011)
Anju Pradhan was added as an author of this paper on 04/03/2011Pyogenic granulomas (PG) are common benign vascular lesions of the skin and mucosa. They are neither infective, purulent nor granulomatous as the name might suggest-rather a reactive enlargement that is an inflammatory response to local irritation such as calculus, fractured tooth, minor trauma, rough dental restorations and foreign materials. Here, we report a case of 13 year old patient with PG and in addition to the knowledge, the importance of biopsy findings in establishing definitive diagnosis has been emphasized. Keywords: pyogenic granuloma; inflammatory hyperplasia; lobular capillary hemangioma. DOI: 10.3126/hren.v8i3.4215Health Renaissance, September-December 2010; Vol 8 (No.3);196-198